Suppression of PTRF Alleviates Post-Infectious Irritable Bowel Syndrome via Downregulation of the TLR4 Pathway in Rats - Zhou, Hui-hui; Zhang, Ye-ming; Zhang, Sheng-peng; Xu, Qi-xiang; Tian, Ya-qing; Li, Ping; Cao, Di; Zheng, Yong-qiu (Frontiers in Pharmacology, 2021)
Background: Post-infectious irritable bowel syndrome (PI-IBS) is a common functional GI disorder that occurs after acute GI infection. Here, we elaborated the role of Polymerase I and Transcript Release Factor (PTRF) in the occurrence of PI-IBS and analyzed its mechanism. Methods: LPS at concentrations of 5μg/ml were used to induce inflammatory injury in HCoEpiC cells. Furthermore, a rat model of PI-IBS was used to study the role of PTRF. Intestinal sensitivity was assessed based on the fecal water content. Two-bottle sucrose intake test was used to evaluate the behavioral changes. Furthermore, shRNA mediated knockdown of PTRF was performed in vitro and in vivo. We detected the expressions of PTRF in colonic mucosal tissues by immunohistochemistry (IHC), western blotting (W-B) and Immunofluorescence (IF). Luciferase activity was quantified by a luciferase assay system. The co-localization of PTRF and TLR4 was detected by IF. The activation of TLR4 down-stream signaling, including the iNOs, p38, ERK, and JNK pathways, was detected by WB. The levels of NO, IL-1β, IL-6 and TNF-α were measured by ELISA. Result：LPS at concentrations of 5μg/ml can significantly induce PTRF expression and TLR4 down-stream signaling, including the p38, ERK, and JNK pathways activation in HCoEpiC cells. Meanwhile, shRNA mediated knockdown of PTRF in HCoEpiC cells significantly decreased p-JNK, p-ERK, and p-p38 phosphorylation and iNOS expression. In PI-IBS rats, lack of PTRF not only reduced fecal water content and suppressed the depressive behavior, but also increased the body weight. Furthermore, we found a strong co-localization pattern for PTRF and TLR4. Consistent with this, lack of PTRF impaired the TLR4 signaling, as shown by the decreased p-JNK, p-ERK, and p-p38, which are upstream factors involved in iNOS expression. Conclusion: PTRF promotes PI-IBS and stimulates TLR4 signaling in vitro and in vivo. The results of this study will not only enrich the pathogenesis of PI-IBS but also make us understand the biological activity of PTRF and provide important experimental basis for PI-IBS clinical treatment targeting PTRF